Analysis of the Village Financial Information System on Village Fund Management Accountability - Ervina Rahayu; Imelda Dian Rahmawati (Indonesian Journal of Cultural and Community Development, 2022)
The existence of a regional autonomy policy makes the Village Government faced with demands to be independent in managing the resources and potentials that exist in the Village, but this is also a gap for fraud in village financial management. Then the existence of the Village Financial System application launched by the Central Government is expected to be able to realize accountability for financial reports in the Village, so that the problem raised by the researcher is the application of the Village Financial System to the accountability of village fund management. The research method used is a qualitative method with an interpretive approach where data collection is in the form of primary data, namely by participatory observation and open interviews and secondary data sources through documents related to research. The results of the study show that the existence of the Siskeudes application facilitates the performance of village officials in managing village finances, although its application does not fully refer to Permendagri No. 20 of 2018. However, accountability in managing village funds can be realized and is one tool to minimize fraud.